Epilepsia parcial fármaco-resistente - Paganini, Lisandro; Besada, Cristina; Ciraolo, Carlos; Silva, Walter; García, María del Carmen; Aberastury, Marina (Revista del Hospital Italiano de Buenos Aires, 2010)
.